WhatsApp Messenger as a Supplementary Tool for School Curriculum Knowledge Transfer and Acquisition During COVID-19 Stricter Lockdown: Educators’ Perceptions - Nkambule, Bongani Innocent (Research in Social Sciences and Technology, 2023)
The COVID-19 pandemic was unarguably one of the most disastrous events whose detriment to the normalcy of the education and training sectors will never be forgotten. To salvage the academic year, the Department of Basic Education (DBE) encouraged historically disadvantaged schools to explore rotational learning supplemented by mobile learning (with WhatsApp Messenger as schools’ most preferred application). However, in face of the concerns that were raised by the media, educational commentators, student bodies and teacher unions about the lack of public schools’ readiness for mobile learning, this social constructivist oriented qualitative study (which drew on 12 educators’ diverse and convergent views) adopted a Technology Acceptance Model (TAM) as a lens to investigate educators’ perceptions of WhatsApp messenger as a supplementary mode of curriculum knowledge transfer and acquisition during COVID 19 stricter lockdown at three historically disadvantaged schools in South Africa. Participants generally deposited positive feedback regarding the benefit of using it WhatsApp messenger to engender curriculum knowledge transfer and acquisition. They however explicitly also detailed a few negative aspects of this pursuit, primarily on how for socio-economic related reasons, the process was not completely inclusive as some learners could not partake in it. Also, educators admitted that while going beyond the call of duty was necessary during the pandemic, WhatsApp mediated teaching consumed most of their leisure time. According to them, this was compounded by poor internet connectivity due to the country’s power crisis, which in some instances adversely affected the productivity of WhatsApp messenger mediated curriculum knowledge transfer and acquisition processes during COVID-19 stricter lockdown.